Design, Optimization and Prototype of a Multi-Phase Fractional Slot Concentrated Windings Surface Mounted on Permanent Magnet Machine - Amir Nekoubin; Jafar Soltani; Milad Dowlatshahi (Majlesi Journal of Electrical Engineering)
The multi-phase permanent-magnet motors are suitable choices for certain purposes like aircrafts, marine, and electric vehicles due to the fault tolerance and high-power density capabilities. The paper aims to design and prototype an optimized five-phase fractional slot concentrated windings surface mounted permanent magnet motor. To optimize the designed multi-phase motor, a multi-objective optimization technique based on the genetic algorithm method has been applied. The machine design objectives are to minimize mass and loss, subsequently, to determine the best choice of the designed machine parameters. Afterwards, 2-Dimensional Finite Element Method (2D-FEM) has been used to verify the performance of the optimized machine. Finally, the optimized machine has been prototyped. The results of the prototyped machine have validated the results of the theatrical analyses of the machine, and accurate consideration of the parameters improved the performance of the machine.